Multiple autoimmune syndrome (Gravesâ€™ disease, systemic lupus erythematosus, and systemic sclerosis) in a young woman in Jakarta - Sumartini Dewi; Bambang Setiyohadi; M I Mokoagow (Indonesian Journal of Rheumatology, 2010)
Multiple autoimmune syndrome (MAS) is a condition in which patients have at least threedistinct autoimmune conditions. The definition of MAS is based on 91 reported cases of such associations in the literature. A review of the literature and cluster analysis of MAS disclosed systemic lupus erythematosus (SLE), SjÃ¶grenâ€™s syndrome, and autoimmune thyroid disease (AITD) as the â€œchaperonesâ€ of autoimmune diseases. This entity was described by Humbert and Dupond in 1988 as a syndrome consisting of the presenceof three or more autoimmune diseases in a single patient. While describing the syndrome, their observations led them to a rough classification of clusters based on the co-occurrence of autoimmune disease, which they identified as types one through three.1 In MAS-1, the authors grouped myasthenia gravis, thymoma, dermatopolymyositis, and autoimmune myocarditis together. In MAS-2, they grouped SjÃ¶grenâ€™s syndrome, rheumatoid arthritis,primary biliary cirrhosis, systemic sclerosis (SSc), and AITD. MAS-3 consists of AITD, myasthenia gravis and/or thymoma, SjÃ¶grenâ€™s syndrome, pernicious anemia, idiopathic thrombocytopenic purpura, Addisonâ€™s disese, type 1 diabetes, vitiligo, autoimmune hemolytic anemia, and SLE.1,2,3 The importance of this concept is the probability thathaving three autoimmune diseases simultaneously in one patient goes beyond epidemiological inferences or statistical chance. Disorders of autoimmune pathogenesis occur with increased frequency in patients with a history of another autoimmune disease. The tendency to develop another disease occurs in about 25% of these patients.3,4 We report a case in which the presence of Gravesâ€™ disease/AITD, SLE, vasculitis, and SSc with pulmonary hypertension and Raynaudâ€™s phenomenon in one patient